Conversion “V” Profiles in Torticollis - M. Jahanshahi; C. D. Marsden (Behavioural Neurology)
The assumption that spasmodic torticollis represents a conversion reaction was examined by evaluating profiles of 61 patients on the hypochondriasis, depression, and hysteria scales of the Minnesota Multiphasic Personality Inventory. Thirty-six per cent of the sample had normal profiles. A conversion “V” profile with scores above 70 was found in a minority (9%) of the patients. The profile of the majority of the group was characterized by the presence of mild depression. It was concluded that a personality profile suggestive of conversion reaction is not typical of patients with spasmodic torticollis.